2004
DOI: 10.1128/mcb.24.8.3396-3403.2004
|View full text |Cite
|
Sign up to set email alerts
|

Melanocytes and Pigmentation Are Affected in Dopachrome Tautomerase Knockout Mice

Abstract: The tyrosinase family comprises three members, tyrosinase (Tyr), tyrosinase-related protein 1 (Tyrp1), and dopachrome tautomerase (Dct). Null mutations and deletions at the Tyr and Tyrp1 loci are known and phenotypically affect coat color due to the absence of enzyme or intracellular mislocalization. At the Dct locus, three mutations are known that lead to pigmentation phenotype. However, these mutations are not null mutations, and we therefore set out to generate a null allele at the Dct gene locus by removin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
100
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 118 publications
(106 citation statements)
references
References 41 publications
(53 reference statements)
4
100
0
Order By: Relevance
“…TRP-2 (dopachrome tautomerase) is a critical enzyme for pigment synthesis in melanocytes (19). We previously reported that mice sensitized to a GM-CSF-expressing B16 vaccine and treated with anti-CTLA-4 developed an anti-TRP-2 180 -188 T cell response.…”
Section: Blockade Of Ctla-4 During Vaccination Enhances Ag-specific Imentioning
confidence: 99%
“…TRP-2 (dopachrome tautomerase) is a critical enzyme for pigment synthesis in melanocytes (19). We previously reported that mice sensitized to a GM-CSF-expressing B16 vaccine and treated with anti-CTLA-4 developed an anti-TRP-2 180 -188 T cell response.…”
Section: Blockade Of Ctla-4 During Vaccination Enhances Ag-specific Imentioning
confidence: 99%
“…CAG-CAT-EGFP mice (a gift from J. Miyazaki, Osaka University, Osaka, Japan) (Kawamoto et al, 2000) were bred with Dct tm1(Cre)Bee mice (a gift from F. Beermann, Swiss Institute for Experimental Cancer Research, Epalinges, Switzerland) to generate compound heterozygotes (Yonetani et al, 2008;Osawa et al, 2005). Genotyping was performed as described previously (Guyonneau et al, 2004).…”
Section: Animalsmentioning
confidence: 99%
“…DCT-deficient mice 43 were bred at McMaster University. All of our investigations have been approved by the McMaster Animal Research Ethics Board.…”
Section: Micementioning
confidence: 99%